Analysis of IVF/ICSI Outcomes in Endometriosis Patients With Recurrent Implantation Failure: Influence on Cumulative Live Birth Rate - Zhong, Chenyi; Gao, Liusijie; Shu, Li; Hou, Zhen; Cai, Lingbo; Huang, Jie; Liu, Jiayin; Mao, Yundong (Frontiers in Endocrinology, 2021)
Abstract Objective: To study the influence of endometriosis activity on the pregnancy outcomes of patients with recurrent implantation failure (RIF) in in-vitro fertilization/intra-cytoplasmic sperm injection (IVF/ICSI) cycles. The pregnancy outcomes were compared between RIF patients with endometriosis who received treatment at different occasions to explore the appropriate treatment plan for these patients and to optimize the pregnancy-support strategies. Design: Ambispective cohort study. Methods: A total of 330 patients with endometriosis were enrolled from 2008 to 2018 and included 1043 IVF/ICSI cycles. All patients were diagnosed with RIF after IVF/ICSI. Patients were assigned to three subtypes according to different control states of endometriosis, including the untreated, early-treatment, and late-treatment groups. The clinical pregnancy rate, live birth rate, and cumulative live birth rate of endometriosis patients with RIF were the main outcomes; additionally, the fertilization rate, available embryonic rate, and high-quality embryonic rate were also compared. Results: The early-treatment and late-treatment groups showed higher cumulative live birth rate than the untreated group (early-treated 43.6% vs. late-treated 46.3% vs. untreated 27.7%, P<0.001), though patients in the two treatment groups had higher rates of adenomyosis and ovarian surgery. The two treatment group showed a better laboratory result than the untreated and especially, the early-treatment group. The untreated group (46.24%) had a lower IVF fertilization rate than the treated group (early-treated [64.40%] and late-treated [60.27%] (P<0.001). In addition, the rates of available embryos and high-quality embryos in the early-treated group were much higher than that in the untreated group (90.30% vs. 85.20%, 76.50% vs. 64.47%). Kaplan–Meier curve showed that patients in the untreated group needed a mean of 23.126 months to achieve one live birth; whereas those in the treated group needed a comparatively shorter duration (early-treated: 18.479±0.882 months and late-treated: 14.183±1.102 months, respectively). Conclusion: Endometriosis has a negative influence on IVF/ICSI outcome. The control of endometriosis activity can result in a higher cumulative live birth rate in patients. It is necessary for endometriosis patients to receive medical treatment to achieve a better prognosis especially for those with RIF.